ABOLISIONISME TINDAK PIDANA DENGAN ANCAMAN PIDANA SINGKAT - Surianti Ningsih, Ni Komang; Sandhi Sudarsana, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
This paper is about Abolitionism criminal offense to a penalty shortly. Theproblems that occurred that imprisonment is often cause social problems especially forthe criminal to a penalty so the need to brief the media Abolitionism other punishment.This paper aims to understand and know about Abolitionism criminal offense to apenalty shortly. This writing, using the method of the normative legal research with thiskind of approach to the analysis of legal concepts. The reason is because the use ofnormative void norms in national rules concerning the offenses Abolitionism short. Thispaper presented a study that looked at Abolitionism is understood that the CriminalJustice System as structural defects as well as the form of punishment in prison as aform of social problem that needed an alternative to criminal prosecution. Understandabolosionisme can dterapkan considering the negative impact of imprisonment. Thenegative impact is exactly what encourages looking for an alternative to criminalprosecution. Special to the crime by the threat of criminal punishment should findalternative short as a consequence of the darkness of the prison world. One alternativethat can be used are fined. For additional fines give the state treasury. It is concludedthat the need Abolitionism of the offenses punishable with alternative sentencing brieffined.
Keywords: Abolitionism, Crime, Criminal Brief